Intracoronary Imaging, Cholesterol Efflux, and Transcriptomes After Intensive Statin Treatment: The YELLOW II Study - Kini, Annapoorna S; Vengrenyuk, Yuliya; Shameer, Khader; Maehara, Akiko; Purushothaman, Meerarani; Yoshimura, Takahiro; Matsumura, Mitsuaki; Aquino, Melissa; Haider, Nezam; Johnson, Kipp W; Readhead, Ben; Kidd, Brian A; et al. (Journal of the American College of Cardiology, 2017)
Despite extensive evidence demonstrating the beneficial effects of statins on clinical outcomes, the mechanisms underlying these effects remain elusive. This study assessed changes in plaque morphology using intravascular imaging, with a comprehensive evaluation of cholesterol efflux capacity (CEC) and peripheral blood mononuclear cell (PBMC) transcriptomics in patients receiving high-dose statin therapy. In a prospective study, 85 patients with stable coronary artery disease underwent percutaneous coronary intervention for a culprit lesion, followed by intracoronary multimodality imaging, including optical coherence tomography (OCT) of an obstructive nonculprit lesion. All subjects received 40 mg of rosuvastatin daily for 8 to 12 weeks, when the nonculprit lesion was reimaged and intervention performed. Blood samples were drawn at both times to assess CEC and transcriptomic profile in PBMC. Baseline OCT minimal fibrous cap thickness (FCT) was 100.9 ± 41.7 μm, which increased to 108.6 ± 39.6 μm at follow-up, and baseline CEC was 0.81 ± 0.14, which increased at follow-up to 0.84 ± 0.14 (p = 0.003). Thin-cap fibroatheroma prevalence decreased from 20.0% to 7.1% (p = 0.003). Changes in FCT were independently associated with CEC increase by multivariate analysis (β: 0.30; p = 0.01). PBMC microarray analysis detected 117 genes that were differentially expressed at follow-up compared to baseline, including genes playing key roles in cholesterol synthesis (SQLE), regulation of fatty acids unsaturation (FADS1), cellular cholesterol uptake (LDLR), efflux (ABCA1 and ABCG1), and inflammation (DHCR24). Weighted coexpression network analysis revealed unique clusters of genes associated with favorable FCT and CEC changes. The study demonstrated an independent association between fibrous cap thickening and improved CEC that may contribute to morphological changes suggesting plaque stabilization among patients taking intensive statin therapy. Furthermore, the significant perturbations in PBMC transcriptome may help determine the beneficial effects of statin on plaque stabilization. (Reduction in Coronary Yellow Plaque, Lipids and Vascular Inflammation by Aggressive Lipid Lowering [YELLOW II]; NCT01837823).